Supporting Second Generation Biofuel Development: Thermophilic Anaerobic Digestion of Vinasse for Harmonizing with Molasses Based Bioethanol Plant Capacity - Nina Anggita Wardani; Wiratni Budhijanto (Eksergi, 2023)
First-generation biofuel is environmental quandary due to its impact to the forest conversion into plantation area. Not only environmental sector, first-generation biofuel has other issues on socioeconomic sector. It consumes crops as its feedstock which will be a conflict between food and energy source. This conflict will impact the vulnerable people as the raising food price. Molasses-based bioethanol is second-generation biofuel which more beneficial from environmental, economic, and social aspect. Molasses-based bioethanol production process generates waste named vinasse. Vinasse can’t be directly discharged to the environment due to its high organic matter concentration which is harmful to the waterbody, soil, and air. On the other hand, high organic matter contained in vinasse can be converted into biogas and is higher potential for molasses-based bioethanol plant. This study was preliminary study for processing vinasse using thermophilic anaerobic digestion specifically by temperature direct escalation and starvation method to the mesophilic originated inoculum. The result shows robust performance of thermophilic microbia which is an averment of compatible method for enriching thermophilic anaerobic microbia in mesophilic originated inoculum.